The Analysis of Human Development Index: Concept and Factors that Influenced in North Sumatera Province - Muammar Rinaldi (Proceedings of AICS - Social Sciences, 2017)
In 2010 the United Nations Development Program (UNDP) re-issued a new version by changing the methodology of calculating the Human Development Index (HDI) from Adult Literacy Rate (ALR) to Expected Year of Schooling (EYS). This improvement is expected to be able one of important indicators in the effort to build the quality of human life and improve the standard of Human Development Index. This study aims to see the impact of unemployment, per capita income, education, and health in influencing the human development index in North Sumatra. The method of analysis that used in this research is Error Correction Model (ECM) method to see the short and long term influence among research variables. The results showed that the value of ECT coefficient on the model have significant and negative of -0.337459 for estimation of Human Development Index. The ECM results also showed that in the short and long term the variables that used in this study significantly influence the human development index, with Adjusted R-squared 0,638 or 63,8% and the remains is 36,2% influenced by other variables outside the study.